Investigating the impact of pandemic job stress and transformational leadership on innovative work behavior: The mediating and moderating role of knowledge sharing - Muhammad Asim Rafique; Yumei Hou; Muhammad Adnan Zahid Chudhery; Muhammad Waheed; Tayyaba Zia; Faiza Chan (Journal of Innovation & Knowledge (JIK), 2022)
Only a few studies have been conducted on job stress and transformational leadership (TL), particularly in the environment of the COVID-19 pandemic. This study aims to overcome this gap and attempts to explore the impact of pandemic job stress (PJS) and TL on employees' innovative work behavior (IWB) through knowledge sharing (KNS), while focusing on the importance of innovations for organizational survival and growth. The data were collected from 357 faculty members of higher education institutions in Pakistan and analyzed using the partial least squares estimation, a structural equation modeling (PLS-SEM) technique. The results demonstrate that PJS positively impacts employees' IWB, negating the negative relationship between job stress and IWB found in previous studies. Moreover, this study found a positive impact of TL and KNS on IWB. KNS also moderates the relationship between PJS and IWB while partially mediating the relationship between TL and IWB. Lastly, the theoretical and practical implications are discussed.
Keywords: 650; Knowledge sharing; Higher education; Innovative work behavior; Pandemic-induced job stress; Transformational leadership